2020
DOI: 10.1007/s11657-020-0692-0
|View full text |Cite
|
Sign up to set email alerts
|

Successful implementation of a Fracture Liaison Service through effective change management: a qualitative study

Abstract: We assessed the context in which a hip Fracture Liaison Service was implemented. We conducted semi-structured interviews with 21 key informants at two time points to understand organizational readiness, facilitators, and barriers to change. We identified strategies important to successful implementation, particularly in the context of change fatigue. Purpose Fracture Liaison Service (FLS) is effective for secondary fracture prevention. Two hospital sites implemented FLS for hip fracture patients, 50 + years, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The quantitative studies and mixed methods studies which included a quantitative arm were critically appraised to be of high quality. Only two of the mixed methods studies failed to provide depth in details about the participants and settings (Lind et al, 2018; Wozniak et al, 2020). In the text and opinion articles the authors clearly identified their opinions which were based on expertise and interest.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The quantitative studies and mixed methods studies which included a quantitative arm were critically appraised to be of high quality. Only two of the mixed methods studies failed to provide depth in details about the participants and settings (Lind et al, 2018; Wozniak et al, 2020). In the text and opinion articles the authors clearly identified their opinions which were based on expertise and interest.…”
Section: Resultsmentioning
confidence: 99%
“…When the focus is on the quantity of change, not quality, this can lead to unintended consequences and change fatigue (Brown & Abuatiq, 2020; Camilleri et al, 2019; Kapping, 2021; Wozniak et al, 2020). Authors reported saturation effect or lack of lulls between changes can lead to change fatigue (Brown et al, 2018; McMillan & Perron, 2020b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The others were arguably intended for a more medical audience [ 22 , 23 ]. Previous qualitative research has highlighted confusion over the roles of FLS clinicians and other clinicians involved in osteoporosis care [ 40 , 41 ]. Statements relating to physical examination were rated as being of relatively low importance by clinicians, and free-text comments supported the assertion that some FLS clinicians do not perceive this as a core part of their role.…”
Section: Discussionmentioning
confidence: 99%
“…The BJH SCNs Shoulder Access Project is one of 16 strategic clinical networks established between Alberta’s healthcare system, researchers, and other key partners who have the expertise to improve health outcomes across the province, foster health promotion, and advance prevention work [ 11 ]. Several other projects have already demonstrated success in improved system processes such as reduced waiting times, improved efficiency of healthcare resources, and improved patient outcomes for patients presenting with hip and knee joint arthritis, hip fractures, back pain, and acute knee injuries [ 11 , 17 – 19 ]. ABJHI is an independent research institute that applies research, data analysis, and measurement by working with healthcare partners such as the BJH SNC to deliver evidence-based, long-term solutions that tangibly improve patient care and patient health.…”
Section: Introductionmentioning
confidence: 99%